2019
DOI: 10.21061/jte.v31i1.a.1
|View full text |Cite
|
Sign up to set email alerts
|

The Demise of Traditional Technology and Engineering Education Teacher Preparation Programs and a New Direction for the Profession

Abstract: For nearly 40 years, there has been a serious decline in the number of new technology and engineering education teachers and teacher preparation programs in the United States (Akmal, Oaks,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…He asserted that short, oneweek, or multi-week summer training institute models being implemented to teach out-of-content area educators how to deliver T&E curricula from organizations like Project Lead the Way (PLTW) were undermining the basis for high-quality and specialized preparation experiences traditionally offered by four-year undergraduate T&E TPPs. In support of these claims, Volk (2019) presented research demonstrating that alternatively certified teachers leave the profession at higher rates, and principals perceive these teachers to be underprepared and less effective compared to teachers who graduated from traditional T&E TPPs. He concluded that while programs like PLTW were often well supported by Perkins funding and helped prevent the closure of T&E programs in P-12 schools due to the shortage of T&E educators, it undermined the basis for TPPs and highly-qualified educators.…”
Section: Alternative Licensure Models: a Slippery Slopementioning
confidence: 99%
See 4 more Smart Citations
“…He asserted that short, oneweek, or multi-week summer training institute models being implemented to teach out-of-content area educators how to deliver T&E curricula from organizations like Project Lead the Way (PLTW) were undermining the basis for high-quality and specialized preparation experiences traditionally offered by four-year undergraduate T&E TPPs. In support of these claims, Volk (2019) presented research demonstrating that alternatively certified teachers leave the profession at higher rates, and principals perceive these teachers to be underprepared and less effective compared to teachers who graduated from traditional T&E TPPs. He concluded that while programs like PLTW were often well supported by Perkins funding and helped prevent the closure of T&E programs in P-12 schools due to the shortage of T&E educators, it undermined the basis for TPPs and highly-qualified educators.…”
Section: Alternative Licensure Models: a Slippery Slopementioning
confidence: 99%
“…Scott and Buffer (1995) predicted political and economic demands would threaten the survival of technology education as a profession. Similar concerns were reiterated more than 20 years later as T&E TPPs continued to face drastically declining program and enrollment trends (Love et al, 2016;Moye, 2017;Volk, 2019). As highlighted by Volk (2019), there are several certification, degree, and coursework pathways beyond traditional undergraduate TPPs that are becoming increasingly popular in attempts to address the critical shortage of T&E educators.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations